A cross-sectional study on the impact of parental educational level and gender differences on emotional and behavioural difficulties in adolescents in Qatar - Maha Al-Hendawi (17337730) (2023)
Heterogeneous findings on the prevalence of emotional and behavioural difficulties (EBD) have been reported in Middle Eastern countries. Moreover, the prevalence of EBD among adolescents in Qatar is unknown, making it difficult to implement the necessary educational or psychosocial programs. This study used a cross-sectional methodology to assess emotional and behavioural problems among 533 high school students from the public government schools. Only 10.6% of the students were found to have EBD, and the prevalence varied significantly in different EBD subscales, as identified using the Strengths and Difficulties Questionnaire (SDQ). The reliability of the scales was good. The population of this study had lower mean EBD scores than those reported in three other Middle Eastern countries. There were significant differences in EBD between males and females, with a higher prevalence in females. No effect of parental education was observed, suggesting that in a society with high economic stability and an excellent social structure, parental education may not be an independent factor influencing the EBD in adolescents. More studies are needed to confirm this hypothesis; however, the findings of the current study will be of importance in establishing the use of the SDQ as a tool for gauging EBD and prioritising necessary interventions. Other Information Published in: Emotional and Behavioural Difficulties License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13632752.2023.2171349